2016
DOI: 10.1111/myc.12556
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility testing of Malassezia yeast: comparison of two different methodologies

Abstract: All Malassezia species are lipophilic; thus, modifications are required in susceptibility testing methods to ensure their growth. Antifungal susceptibility of Malassezia species using agar and broth dilution methods has been studied. Currently, few tests using disc diffusion methods are being performed. The aim was to evaluate the in vitro susceptibility of Malassezia yeast against antifungal agents using broth microdilution and disc diffusion methods, then to compare both methodologies. Fifty Malassezia isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
30
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
6
30
2
1
Order By: Relevance
“…[15] The good in vitro activity of itraconazole shown in this study makes it a possible choice for the treatment of Malassezia related infections in this particular geographic area. In agreement with other reports, this study also found higher in vitro antifungal activity against all the tested clinical isolates of Malassezia spp, with itraconazole.…”
Section: Resutsmentioning
confidence: 99%
See 4 more Smart Citations
“…[15] The good in vitro activity of itraconazole shown in this study makes it a possible choice for the treatment of Malassezia related infections in this particular geographic area. In agreement with other reports, this study also found higher in vitro antifungal activity against all the tested clinical isolates of Malassezia spp, with itraconazole.…”
Section: Resutsmentioning
confidence: 99%
“…These results are similar to or higher than those documented in various other studies. [15,18,19] MIC ranges against itraconazole shown in several studies are as follows: < 0.03-16µg/mL, [16] 0.007 -0.05μg/mL, [19] 3µg/mL -0.125µg/mL [6] and ≤ 0.03 -0.06 µg/mL. [4] Gupta AK et al [17] found the MIC data obtained for itraconazole were similar to MICs for itraconazole and ketoconazole with an MIC of 0.8µg/ml for both.…”
Section: Resutsmentioning
confidence: 99%
See 3 more Smart Citations